Highly biocompatible Co@Silica@meso-Silica magnetic nanocarriers - Wu, Si-Ming; Jiang, Nan; Hu, Zhi-Yi; Yan, Tao; Jin, Jun; Geng, Wei; Yang, Xiao-Yu (Chemical Physics Letters, 2019)
Core-shell structured Co@Silica@meso-Silica nanoparticles have been synthesized via a layer-by-layer approach. The magnetic cobalt core makes the nanoparticles easy to separate with an external magnetic field. The inner dense silica layer prevents the Co from oxidation and leaching. The outer mesoporous silica presents high surface area and pore volume, endowing the material with superior adsorption properties of organic molecules. The core-shell structure prevents the direct contact of cobalt with living cells, thus enhancing the biocompatibility remarkably. This dual encapsulation provides a golden opportunity to the nanocarrier design with easy magnetic separation, high drug loading, and high biocompatibility.
Created from Fastlane, Scopus look-up
Keywords: Biocompatibility; Cobalt nanoparticles; Core-shell structure; Magnetic materials; Mesoporous silica; Nanocarrier